The potential of biodiesel in mitigating the energy crisis in Sub-Saharan Africa energy sectors - Michael Lanre Adekanbi; Banji Titilope Ibukun; Eshiemogie Steve (Sustinere: Journal of Environment and Sustainability, 2021)
As a result of the damaging effects they have on the climate, recent campaigns against fossil fuels, constantly emphasize the need to completely eliminate their use. To this effect, is a pressing need to source for other sources of energy that have the ability to decrease the level of greenhouse gas emissions to the atmosphere. These alternatives have to be easily accessible and should contribute to the industrial expansion of developing regions, especially Sub-saharan Africa. Poor access to electricity is a major challenge that contributes to the retarded state of development of some countries in Sub-saharan Africa, and renewable energy alternatives, such as biofuels, can perfectly solve this oddity. Biofuels possess unique attributes that can help the world attain a state of energy security and energy balance. The depletion of fossil fuels and other factors like technological advancement and current industrial expansion occurring in most countries in Sub-saharan Africa poses a threat to the availability of energy in the region and it is a major setback to the achievement of the United Nation's Sustainable Development Goal 7. Narrowing down to the use of biodiesels, implementing their use can save the continent from a lot of damage and build up a more sustainable energy sector. Massive deployment of Biodiesels into the energy sector of Sub-saharan Africa will not only ease the difficulty in accessing energy, it will also boost the agricultural sector and economy of the countries that constitute the region. This paper reviews the current state of biodiesel in the African sub-saharan region.